Genotype–phenotype relationship in Japanese patients with congenital central hypoventilation syndrome - Shimokaze, Tomoyuki; Sasaki, Ayako; Meguro, Toru; Hasegawa, Hisaya; Hiraku, Yuka; Yoshikawa, Tetsushi; Kishikawa, Yumiko; Hayasaka, Kiyoshi (Journal of human genetics, 2015)
Examine the genotype-phenotype relationship in Japanese congenital central hypoventilation syndrome (CCHS) patients and estimate the incidence of CCHS in Japan. Subjects were 92 Japanese patients with PHOX2B mutations; 19 cases carried 25 polyalanine repeat expansion mutations (PARMs); 67 cases carried 26 or more PARMs; and 6 had non-PARMs (NPARMs). We collected clinical data in all patients and estimated the development or intelligent quotients only in the patients carrying 25 PARM. The estimated incidence of CCHS was greater than one case per 148 000 births. Polyhydramnios was observed in three cases. Twelve infants exhibited depressed respiration at birth. In 19 cases carrying 25 PARM, the male-to-female ratio was ~3, no cases had Hirschsprung disease; 7 cases (37%) developed hypoventilation after the neonatal period, and 8 cases (42%) had mental retardation. In other 73 cases carrying 26 or more PARMs or NPARMs, male-to-female ratio was equal; patients frequently complicated with Hirschsprung disease and constipation, and all patients presented with hypoventilation in the neonatal period. Clinical symptoms were severe in most patients carrying long PARMs and NPARMs. In 25 PARM, additional genetic and/or epigenetic factors were required for CCHS development and male sex is likely a predisposing factor. The patients carrying 25 PARM frequently had mental retardation likely because they were not able to receive appropriate ventilation support following a definitive diagnosis owing to subtle and or irregular hypoventilation. Molecular diagnosis provides a definitive diagnosis and enables to receive appropriate ventilator support.